Tunable Transfer‐Hydrodeoxygenated Upgrading of Lignin‐Derived Propylphenols to Versatile Value‐Added Alkane‐Based Chemicals - Yanyan Yu; Yilin Li; Yuhan Lou; Mengyuan Chen; Yongzhuang Liu; Haipeng Yu (Advanced Science)
Abstract Catalytic refining of lignin holds promise for producing sustainable platform chemicals. In this work, a gaseous hydrogen‐free catalytic hydrodeoxygenation system is developed for upgrading lignin‐derived phenols to alkane chemicals. Commercially available Raney Ni and HZSM‐5 are used as a combinational catalyst, with isopropanol serving as the hydrogen‐donating solvent. By modifying the temperature and the ratio of Raney Ni to HZSM‐5, the reaction pathways for hydrogenation and deoxygenation can be tailored to specific requirements. As a result, a 97.1% yield of alkane fuels is achieved, with 64.4% propylcyclohexane and 32.7% propylbenzene obtained in one‐pot reaction from the hydrodeoxygenation of 2‐methoxy‐4‐propylphenol using a 3:1 mass ratio of Ni to HZSM‐5, further increasing the ratio of HZSM‐5 leads to a selectively production of propylbenzene in 62.0% yield. Through careful regulation of the catalytic system and the design of hydrogenation–deoxygenation pathways, excellent yields of 4‐propylcyclohexanol (92.2%), propylcyclohexene (93.3%), and propylcyclohexane (93.2%) are directionally achieved. The catalyst maintained a conversion rate of over 99% after five cycles, demonstrating excellent robustness. This study offers a strategic system that expedites the selective upgrading of lignin‐derived chemicals, heralding a pathway toward sustainable fuels and chemicals.